Influential Factors on Online Repurchase Intentions: A Study on Tokopedia Marketplace: Faktor-faktor yang Mempengaruhi Niat Pembelian Ulang Secara Online: Studi pada Pasar Tokopedia - Adam Jody Suwarno Suwarno; Lilik Indayani (Academia Open, 2024)
This quantitative study investigates the impact of trust, risk perception, and perceived benefits on online repurchase intentions within the Tokopedia marketplace. Conducted in Sidoarjo, Indonesia, the research sampled individuals who had made multiple purchases on Tokopedia. Findings reveal that trust exerts a positive partial influence on online repurchase intentions, while risk perception and perceived benefits also influence repurchase intentions positively. Collectively, these factors underscore the complex dynamics of consumer behavior in the online marketplace, offering insights for e-commerce platforms and marketers seeking to enhance customer loyalty and repeat purchases. Highlight: This study examines the influence of trust, risk perception, and perceived benefits on online repurchase intentions in the Tokopedia marketplace. Trust plays a significant positive role in shaping online repurchase intentions. Findings provide valuable insights for e-commerce platforms and marketers aiming to foster customer loyalty and repeat purchases in the online marketplace. Keywords: Online Repurchase Intentions,Trust, Risk Perception, Perceived Benefits, Tokopedia Marketplace